Distribution of some important mosquito species in Portugal within the framework of the national program for vector surveillance - REVIVE - Osório, H.C. (2017)
Abstract in: 20th European Society for Vector Ecology Conference 2016: book of abstracts, p. 129. doi:10.3920/978-90-8686-837-7